Tobacco Harm Knowledge and Attitude among Infertile Couples - Mahshid Aryanpur; Majid Tarahomi; Mohamad Mehdi Akhondi; Hooman Sadri Ardakani; Gholamreza Heydari; Mohamad Reza Masjedi (Tehran University of Medical Sciences, 2009)
Objective: High prevalence of tobacco consumption in childbearing ages is an important topic of consideration as its ill effects have influences on fertility. Worldwide studies have shown that general knowledge on fertility issues is low. Aim of the current study was to assess tobacco harm knowledge and attitude in infertile couples referring to the Avicenna center. Materials and Methods: This was a cross-sectional study.  All Avicenna fertility clinics' new patients with infertility complain between November of 2007 and February 2008 was included.  Information was collected trough standard knowledge and attitude questionnaire. Results: Among 684 individuals (342 couples), the mean score of knowledge and attitude was 0.49±0.79 (from a total of 4), 19.1±2.70 (from a total of 24). The mean knowledge score among women and men was 0.44±0.73, 0.54±0.84, respectively. The mean of attitude score in women and men was 19.35±2.55, 18.85±2.82, respectively.  Significant correlation between age, gender, education and tobacco experience with knowledge was not found.  Yet, attitude was significantly more appropriate in women, the educated and inexperienced tobacco usage (P=0.001, P=0.001, P=0.03, respectively). Conclusion: In the population studied, attitude was appropriate but level of knowledge was low and this suggests more steps should be taken to improve the knowledge.